Gamification and Advanced Technology to Enhance Motivation in Education - Llorens-Largo, Faraón; Molina-Carmona, Rafael (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This book, entitled "Gamification and Advanced Technology to Enhance Motivation in Education", contains an editorial and a collection of ten research articles that highlight the use of gamification and other advanced technologies as powerful tools for motivation during learning. Motivation is the driving force behind many human activities, especially learning. Motivated students are ready to make a significant mental effort and use deeper and more effective learning strategies. Numerous studies indicate that playing promotes learning, since when fun pervades the learning process, motivation increases and tension is reduced. Therefore, games can be very powerful tools in the improvement of learning processes from three different and complementary perspectives: as tools for teaching content or skills, as an object of the learning project itself and as a philosophy to be taken into account when designing the training process. Each contributions presented in this book falls into one of these categories; that is to say, they all deal with the use of games or related technologies, and they all study how playing enhances motivation in education.